Competitiveness Enhancement of The Small Enterprises of Dried Three-Spot Gourami (Trichogaster trichopterus) in Banjar Regency, South Kalimantan Province Through Improvement of The Process Technology, Managerial, and Business Culture - Agung Nugroho; Dessy Maulidya Maharani; Agung Cahyo Legowo; Febriani Purba (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Competitiveness enhancement of the dried three spot gourami producers in Banjar Regency, South Kalimantan Province was undertaken, because they are the least beneficiaries of the business system that has been run for generations. The competitiveness was developed through improvement of the production technology, managerial, and business culture. Technology enhancement was achieved by improving the drying method, product diversification, quality improvement, packaging improvement, and labeling. Managerial aspects developed included management in finance, resources, and marketing. Cultural development was focused on social behavior, namely education on the importance of investment and financial management so that the revenue obtained can be used as business assets again. Those efforts have effectively improved the indicators of business competitiveness, namely increasing income, increasing product added value, increasing innovation and creativity, raising awareness of quality, increasing managerial ability, and improving attitudes and enthusiasm for continuous improvement